2018
DOI: 10.1002/14651858.cd012089.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Parent-mediated interventions for promoting communication and language development in young children with Down syndrome

Abstract: Parent-mediated interventions for promoting communication and language development in young children with Down syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 122 publications
0
48
0
1
Order By: Relevance
“…Such prompting should eventually help promote children's spontaneous talk about mental states. Although we do not yet have evidence for caregiver-implemented shared storybook interventions increasing mental state language in children with DS (see O'Toole et al 52 ), results from interventions with other populations, such as fragile X syndrome, are particularly promising. For example, a caregiver-implemented shared storybook intervention for school-age children with fragile X syndrome has been successful in increasing children's mental state and inferential language use.…”
Section: Talk About Mental Statesmentioning
confidence: 92%
“…Such prompting should eventually help promote children's spontaneous talk about mental states. Although we do not yet have evidence for caregiver-implemented shared storybook interventions increasing mental state language in children with DS (see O'Toole et al 52 ), results from interventions with other populations, such as fragile X syndrome, are particularly promising. For example, a caregiver-implemented shared storybook intervention for school-age children with fragile X syndrome has been successful in increasing children's mental state and inferential language use.…”
Section: Talk About Mental Statesmentioning
confidence: 92%
“…However, apart from the more common genetic syndromes, there is a paucity of information about this. 17 18 The American Heart Association reviewed the literature on children with CHD and concluded that they are at an increased risk of developmental delay, even once the frequent occurrence of genetic syndromes has been taken into account, particularly for neonates or infants requiring open heart surgery. 19 Wehby et al also showed that children with isolated orofacial clefts were at a much greater risk of low achievement at school than their classmates.…”
Section: Open Accessmentioning
confidence: 99%
“…Infantile spasms Infant [26] Learning, memory and speech problems Childhood [3] A publication by Dr. Jean-Étienne D. Esquirol in 1838 on mental conditions included a description of persons with DS [29]. Dr. Edouard Seguin, who studied psychiatry under Dr. Esquirol, went on to publish a book on the physiological method of teaching individuals with DS [30], believing DS was caused by weakness in the nervous system to be A publication by Dr. Jean-Étienne D. Esquirol in 1838 on mental conditions included a description of persons with DS [29].…”
Section: Comorbidity Age Referencesmentioning
confidence: 99%
“…Background Down Syndrome (DS) is caused by a complete or segmental triplication of human chromosome 21 (HSA21) [1] and is the most frequent genetic cause of intellectual disability (ID) [2]. People with DS present with developmental abnormalities [3], systemic alterations in the peripheral system, as well as neurological and cognitive deficits (Table 1) [2,[4][5][6]. The most common causes for emergency room (ER) visits in children with DS are ear, nose, and throat issues [7].…”
mentioning
confidence: 99%